PENDIDIKAN POLITIK DALAM PERSPEKTIF AL-QUR’AN DAN HADITS - Siti Rahmah; Iskandar (CV. Adiba Aisha Amira, 2021)
Islam is a perfect religion that not only regulates ritualistic relationships between humans and their creators, but Islam is a comprehensive religion that regulates all aspects of human life both spiritually and physically, as well as regulates human affairs in social life and lays down the principles of the nation and state. State, including matters related to politics, power and government, political education, in political Islam known as siyasa which studies matters concerning matters concerning the affairs of the people and the state with all forms of law, regulation, and policies made by the holder of power. The Qur'an also uses the term Sulthan,